Automotive steering, suspension, and alignment - Halderman, James D. 1943-; Mitchell, Chase D. (Pearson/Prentice Hall, 2004)
This book fills the need for technical information that correlates to the National ASE Certification Test and the NATEF Automotive Program Standards for Automotive Content Area A4. Real world examples help users prepare to take and pass the ASE certification test. (Midwest)